The Analysis of the Effectiveness of Covid-19 Mitigation Policies: A Case Study of Palu City - Slamet Riadi; Awaluddin (Journal of Public Administration and Government, 2023)
Conducted with the aim of assessing the effectiveness of Covid-19 handling policies in Palu City, this study sought to describe and analyze the factors hindering their implementation. Utilizing a qualitative research method, the research focused on understanding the phenomena and symptoms observed in the field. The findings suggest that while the implementation of Covid-19 handling policies in Palu City is moderately effective, it is not optimal due to economic pressures leading many individuals to continue their usual activities without adhering to the policies. Inhibiting factors include the prevalence of Covid-19-related misinformation, disagreements in zone determination, low public awareness of their vulnerability to the virus, insufficient understanding of the benefits of health protocols, and a lack of information and guidance to encourage adherence to health protocols. Additionally, limited access to essential items for implementing health protocols, such as masks, soap, and hand sanitizer, contributes to the suboptimal effectiveness of the policies.